Global prevalence of percutaneous injuries among healthcare workers: A systematic review and meta-analysis - Auta, A.; Adewuyi, Emmanuel; Tor-Anyiin, A.; Edor, J.P.; Kureh, G.T.; Khanal, V.; Oga, E.; Adeloye, D. (2018)
Background: Healthcare workers (HCWs) are at risk of occupational exposure to bloodborne pathogens through contact with human blood and other body fluids. This study was conducted to estimate the global and regional 1-year prevalence of percutaneous injuries (PCIs) among HCWs. Methods: We systematically searched EMBASE, PubMed, CINAHL and PsychInfo databases for studies published from January 2008 to January 2018 that reported the prevalence of PCIs among HCWs. A random-effects meta-analysis was conducted to estimate pooled prevalence of PCIs among HCWs. Results: Of the 5205 articles identified, 148 studies from 43 countries met the inclusion criteria. The pooled global 1-year prevalence estimate of PCIs was 36.4% [95% confidence interval (CI): 32.9–40.0]. There were substantial regional variations in the 1-year prevalence of PCIs, ranging from 7.7% (95% CI: 3.1–12.4) in South America to 43.2% (95% CI: 38.3–48.0) in Asia. The estimates for Africa and Europe were comparable with values of 34.5% (95% CI: 29.9–39.1) and 31.8% (95% CI: 25.0–38.5), respectively. The highest 1-year prevalence by job category was among surgeons, at 72.6% (95% CI: 58.0–87.2). The estimates for medical doctors (excluding surgeons), nurses (including midwives) and laboratory staff (including laboratory technicians) were 44.5% (95% CI: 37.5–51.5), 40.9% (95% CI: 35.2–46.7) and 32.4% (95% CI: 20.9–49.3), respectively. PCIs commonly occurred among HCWs working in hospital (41.8%, 95% CI: 37.6–46.0) than non-hospital (7.5%, 95% CI: 5.9–9.1) settings. Conclusions: Our findings suggest high rates of PCIs among HCWs with direct patient care across many regions of the world. However, paucity of data from some countries was a major limitation.